Pengenalan Penyakit Darah Pada Citra Darah Menggunakan Logika Fuzzy - Endro Andriyanto (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2011)
The blood that flows in the body has the ability present to disease based on blood cell types, so do the introduction of blood diseases with the image recognation method. This is supported by image processing technology that is able to capture image the blood in order to obtain a good image. The image recognation method will be done image processing, so that the data obtained can be analyzed to detect a disease. To build the image recognation method with this blood disease needed an application program. The study used the image recognation method by fuzzy logic method, which will be trained to identified the blood diseases. From the research it is known that leukemia disease can identified by analyzing the color of an image on the blood of a patient with leukemia. Result of that method carried by shaping the character of the image and them made The Introduction of The Fuzzy Inference System